Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)999x1001=(1000-1)(1000+1)=10002-12=1000000-1=999999
b)bạn viết đúng đề câu b k thế?
a ) ( 2x + 1 )2 - 4 ( x + 2 )2 = 9
4x2 + 4x + 1 - 4 ( x2 +4x + 4 ) = 9
4x2 + 4x + 1 - 4x2 -16x -16 = 9
-12x - 15 = 9
-12x = 24
x = -2
b) 3 ( x - 1 )2 - 3x ( x - 5 ) = 1
3 ( x2 - 2x + 1 ) - 3x2 + 15x = 1
3x2 - 6x + 3 - 3x2 + 15x = 1
9x + 3 = 1
9x = -2
x = \(\frac{-2}{9}\)
4: \(D=x^2-2\cdot x\cdot\dfrac{1}{2}+\dfrac{1}{4}+\dfrac{3}{4}\)
\(=\left(x-\dfrac{1}{2}\right)^2+\dfrac{3}{4}\ge\dfrac{3}{4}\forall x\)
Dấu '=' xảy ra khi \(x=\dfrac{1}{2}\)
\(A=\left(x^2-6x+9\right)-7=\left(x-3\right)^2-7\ge7\\ A_{min}=7\Leftrightarrow x=3\\ B=\left(9x^2+6x+1\right)-4=\left(3x+1\right)^2-4\ge-4\\ B_{min}=-4\Leftrightarrow x=-\dfrac{1}{3}\\ C=\left(x^2-2\cdot\dfrac{5}{2}x+\dfrac{25}{4}\right)-\dfrac{9}{4}=\left(x-\dfrac{5}{2}\right)^2-\dfrac{9}{4}\ge-\dfrac{9}{4}\\ C_{min}=-\dfrac{9}{4}\Leftrightarrow x=\dfrac{5}{2}\\ D=\left(x^2-x+\dfrac{1}{4}\right)+\dfrac{3}{4}=\left(x-\dfrac{1}{2}\right)^2+\dfrac{3}{4}\ge\dfrac{3}{4}\\ D_{min}=\dfrac{3}{4}\Leftrightarrow x=\dfrac{1}{2}\)
\(E=3\left(x^2+2\cdot\dfrac{1}{3}x+\dfrac{1}{9}\right)-\dfrac{4}{3}=3\left(x+\dfrac{1}{3}\right)^2-\dfrac{4}{3}\ge-\dfrac{4}{3}\\ E_{min}=-\dfrac{4}{3}\Leftrightarrow x=-\dfrac{1}{3}\\ F=x^2-2x+1+x^2-4x+4+2021\\ F=2\left(x^2-3x+\dfrac{9}{4}\right)+\dfrac{4031}{2}=2\left(x-\dfrac{3}{2}\right)^2+\dfrac{4031}{2}\ge\dfrac{4031}{2}\\ F_{min}=\dfrac{4031}{2}\Leftrightarrow x=\dfrac{3}{2}\)
Bài 3:
a) \(A=\left(2xy^2\right)\left(x^3-2xy+2y^2\right)\)
\(A=2xy^2\cdot x^3-2xy^2\cdot2xy+2xy^2\cdot2y^2\)
\(A=2x^4y^2-4x^2y^3+4xy^4\)
b) \(B=\left(x^2+y^2-z^2\right)\left(x^2+y^2+z^2\right)\)
\(B=x^2\cdot x^2+x^2\cdot y^2+x^2\cdot z^2+x^2\cdot y^2+y^2\cdot y^2+y^2\cdot z^2-x^2\cdot z^2-y^2\cdot z^2-z^2\cdot z^2\)
\(B=x^4+x^2y^2+x^2z^2+x^2y^2+y^4+y^2z^2-x^2z^2-y^2z^2-z^4\)
\(B=x^4+\left(x^2y^2+x^2y^2\right)+\left(x^2z^2-x^2z^2\right)+y^4+\left(y^2z^2-y^2z^2\right)-z^4\)
\(B=x^4+y^4-z^4+2x^2y^2\)
c) \(C=-\dfrac{1}{4}xy\left(4x^2y^2-x^2y-\dfrac{4}{5}\right)\)
\(C=-\dfrac{1}{4}xy\cdot4x^2y^2+\dfrac{1}{4}xy\cdot x^2y+\dfrac{1}{4}xy\cdot\dfrac{4}{5}\)
\(C=-x^3y^3+\dfrac{1}{4}x^3y^2+\dfrac{1}{5}xy\)
d) \(D=\left(x-y\right)^4\)
\(D=\left[\left(x-y\right)^2\right]^2\)
\(D=\left(x^2-2xy+y^2\right)^2\)
\(D=\left(x^2-2xy+y^2\right)\left(x^2-2xy+y^2\right)\)
\(D=x^4-2x^3y+x^2y^2-2x^3y+4x^2y^2-2xy^3+x^2y^2-2xy^3+y^4\)
\(D=x^4+6x^2y^2+y^4\)
4/
a/ \(A=\dfrac{7y^5z^2-14y^3z^4+2,1y^4z^3}{-7y^3z^2}=\dfrac{7y^5z^2}{-7y^3z^2}+\dfrac{-14y^3z^4}{-7y^3z^2}+\dfrac{2,1y^4z^3}{-7y^3z^2}=-y^2+2z^2-0,3yz\)
b/ \(A=\dfrac{9x^3y+3xy^3-6x^2y^2}{-3xy}=\dfrac{9x^3y}{-3xy}+\dfrac{3xy^3}{-3xy}+\dfrac{-6x^2y^2}{-3xy}=-3x^2-y^2+2xy\)
Bài 1:
\(a+b=15\)
\(\Rightarrow\left(a+b\right)^2=225\)
\(\Leftrightarrow a^2+2ab+b^2=225\)
\(\Leftrightarrow a^2+4+b^2=225\)
\(\Leftrightarrow a^2+b^2=221\)
Ta có: \(\left(a-b\right)^2=a^2-2ab+b^2\)
\(=221-4\)
\(217\)
Bài 2:
Vì \(x:7\)dư 6
\(\Rightarrow x\equiv-1\left(mod7\right)\)
\(\Rightarrow x^2\equiv1\left(mod7\right)\)
Vậy \(x^2:7\)dư 1
Trả lời:
Bài 2:
a, 64x3 + 48x2y + 36xy2 + 27y3
= (4x)3 + 3.(4x)2.3y + 3.4x.(3y)2 + (3y)3
= ( 4x + 3y )3
b, 1 - 15y + 75y2 - 125y3
= 13 - 3.1.5y + 3.1.(5y)2 - (5y)3
= ( 1 - 5y )3
c, 8x3 + 4x2y + 2/3 xy2 + 1/27 y3
= (2x)3 + 3.(2x)2.1/3 y + 3.2x.(1/3 y)2 + (1/3 y)3
= ( 2x + 1/3 y )3
d, 1/64 - 3/8 y + 3y2 - 8y3
= (1/4)3 - 3.(1/4)2.2y + 3.1/4.(2y)2 - (2y)3
= ( 1/4 - 2y )3
e, ( 2x + 3y )( 4x2 - 6xy + 9y2 )
= ( 2x + 3y )[ (2x)2 - 2x.3y + (3y)2 ]
= (2x)3 + (3y)3
= 8x3 + 27y3
g, ( 3x + 4 )( 9x2 - 12x + 16 )
= ( 3x + 4 )[ (3x)2 - 3x.4 + 42 ]
= (3x)3 + 43
= 27x3 + 64
h, ( 3 - x )( 9 + 3x + x2 )
= ( 3 - x )( 32 + 3.x + x2 )
= 33 - x3
= 27 - x3
i, ( x2 - 1/2 )( x4 + 1/2x2 + 1/4 )
= ( x2 - 1/2 )[ (x2)2 + x2.1/2 + (1/2)2 ]
= (x2)3 - (1/2)3
= x6 - 1/8